The role of visual perception measures used in sports vision programmes in predicting actual game performance in Division I collegiate hockey players - Poltavski, D.; Biberdorf, D. (Journal of Sports Sciences, 2015)
In the growing field of sports vision little is still known about unique attributes of visual processing in ice hockey and what role visual processing plays in the overall athlete`s performance. In the present study we evaluated whether visual, perceptual and cognitive/motor variables collected using the Nike SPARQ Sensory Training Station have significant relevance to the real game statistics of 38 Division I collegiate male and female hockey players. The results demonstrated that 69% of variance in the goals made by forwards in 2011-2013 could be predicted by their faster reaction time to a visual stimulus, better visual memory, better visual discrimination and a faster ability to shift focus between near and far objects. Approximately 33% of variance in game points was significantly related to better discrimination among competing visual stimuli. In addition, reaction time to a visual stimulus as well as stereoptic quickness significantly accounted for 24% of variance in the mean duration of the player`s penalty time. This is one of the first studies to show that some of the visual skills that state-of-the-art generalised sports vision programmes are purported to target may indeed be important for hockey players` actual performance on the ice.